Dostoevsky’s novels as classic tragedies - Egeberg, Erik (Nordlit, 2014)
Friedrich Nietzsche’s treatise “Die Geburt der Tragödie aus dem Geiste der Musik” (1872) has, with the symbolist poet and critic Vyacheslav Ivanov as an important intermediary, exerted a strong influence on Dostoevsky scholarship which can be traced up to this day. The present short paper discusses some aspects of this tradition of interpretation.